2006
DOI: 10.1016/j.nima.2005.12.219
|View full text |Cite
|
Sign up to set email alerts
|

Advances in thick GEM-like gaseous electron multipliers Part II: Low-pressure operation

Abstract: We present results on THGEM operation at low gas pressures, in the range 0.5-50 Torr. Gaseous gain up to 10 5 was recorded at 10 Torr of Isobutane in a single multiplier element, with pulses rise-time in the few ns range. Cascaded operation of two THGEMs is reported, with similar total gain but at lower voltages on each element. The present work encompasses a large variety of THGEM geometries and includes electric-field distribution calculations and electron transport simulations. We discuss the operation mech… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 12 publications
1
53
1
Order By: Relevance
“…The requirement of high voltages needed for maintaining the drift field in the TPC, and for achieving high gas gains in the amplification device, is incompatible with stable operation at low pressures. Nevertheless, high gas gains in micro-patterned gas detectors such as Thick GEMs (THGEMs) have been demonstrated down to ∼ 5 Torr in certain gases [237]. Using such devices, Phan et al [235] have shown sufficiently high gas gains with CS 2 close to 10 Torr.…”
Section: Experimental Prospectsmentioning
confidence: 99%
“…The requirement of high voltages needed for maintaining the drift field in the TPC, and for achieving high gas gains in the amplification device, is incompatible with stable operation at low pressures. Nevertheless, high gas gains in micro-patterned gas detectors such as Thick GEMs (THGEMs) have been demonstrated down to ∼ 5 Torr in certain gases [237]. Using such devices, Phan et al [235] have shown sufficiently high gas gains with CS 2 close to 10 Torr.…”
Section: Experimental Prospectsmentioning
confidence: 99%
“…In the previous [1,23] and in the present works, we have investigated a large variety of THGEM geometries over a broad pressure range (0.5-760 Torr). We will discuss in this and in a following article [24] the optimal geometry in terms of hole diameter, hole spacing and electrode thickness, for different applications at atmospheric and at low gas pressures.…”
Section: Introductionmentioning
confidence: 99%
“…The operation mechanism and properties of the THGEM at atmospheric and at low gas pressure were described in detail in [24], [27]. They can be operated as single-element multipliers or in multi-element (cascaded) mode.…”
Section: Introductionmentioning
confidence: 99%